Help to perpetuate traditional gender roles Benevolent sexism increases engagement in dependency-oriented cross-gender helping. [article]. - Shnabel, Nurit
Based on theorizing that helping relations may serve as a subtle mechanism to reinforce intergroup inequality, the present research(N=1,315) examined the relation between benevolent sexism (i.e., a chivalrous yet subtly oppressive view of women) and helping. In cross-gender interactions, the endorsement of (Studies 1,3 and 4) or exposure to (Study 2) benevolent sexism predicted (a) men's preference to provide women with dependency-oriented help (i.e., direct assistance) rather than tools for autonomous coping, and (b) women's preference to seek dependency-oriented help rather than tools for autonomous coping. Benevolent sexism did not predict men's and women's engagement in dependency-oriented helping relations in same gender-interactions. Studies 1 and 2 examined behavioral intentions in response to a series of hypothetical scenarios; Studies 3 and 4 examined actual behavioral in tests of mathematical and logical ability and pointed to assumed partner's expectations as a potential mediator. The converging evidence supports the hypothesis that benevolent sexism encourages engagement in cross-gender helping relations that perpetuate gender roles. -- (from the authors)